2018
DOI: 10.21307/ane-2018-011
|View full text |Cite
|
Sign up to set email alerts
|

Face processing in a case of high functioning autism with developmental prosopagnosia

Abstract: The ability to "read" the information about facial identity, expressed emotions, and intentions is crucial for non-verbal social interaction.Neuroimaging and clinical studies consequently link face perception with fusiform gyrus (FG) and occipital face area (OFA) activity. Here we investigated face processing in an adult, patient PK, diagnosed with both high functioning autism spectrum disorder (ASD) and developmental prosopagnosia (DP). Both disorders have a significant impact on face perception and recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…We also set aside those papers in which prosopagnosia occurred in combination with other neurocognitive disorders, such as autism spectrum disorder (e.g. Cygan et al, 2018;Fry et al, 2022), cases in which prosopagnosia was a symptom of a broader deficit, such as neurodegenerative disorders (e.g. Ishihara et al, 2021;Singh & Ramanathan, 2023), or occurred as a symptom of a currently under-researched cause such as COVID-19 (Kieseler & Duchaine, 2023).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…We also set aside those papers in which prosopagnosia occurred in combination with other neurocognitive disorders, such as autism spectrum disorder (e.g. Cygan et al, 2018;Fry et al, 2022), cases in which prosopagnosia was a symptom of a broader deficit, such as neurodegenerative disorders (e.g. Ishihara et al, 2021;Singh & Ramanathan, 2023), or occurred as a symptom of a currently under-researched cause such as COVID-19 (Kieseler & Duchaine, 2023).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…It has also been reported that those with ASD have a substantially higher rate of developmental prosopagnosia (DP; up to 36% 1 , Minio-Palluelo, Porciello, Pascual-Leone, and Baron-Cohen, 2020), or severe lifelong face recognition deficits, than the general population prevalence of 2% (Kennerknecht et al, 2006;Behrmann and Avidan, 2005;Duchaine and Nakayama, 2006b;Susilo and Duchaine, 2013). However, the nature and causes of the co-occurrence between ASD traits and DP are poorly characterized (Cygan et al, 2018). The goal of the present study was to examine whether DPs with higher levels of autism traits (i.e., broader autism phenotype, Wheelwright, Auyeung, Allison, and Baron-Cohen, 2010;Landry and Chouinard, 2016) differ from DPs with lower levels of autism traits across a broad battery of assessments, including face memory, face perception, holistic face processing, eye and mouth processing, emotion recognition, and in their fMRI selectivity and connectivity of face processing regions.…”
mentioning
confidence: 99%
“…It has also been reported that those with ASD have a substantially higher rate of developmental prosopagnosia (DP; up to 36% 1 , Minio-Palluelo, Porciello, Pascual-Leone, and Baron-Cohen, 2020), or severe lifelong face recognition deficits, than the general population prevalence of 2% (Kennerknecht et al, 2006;Behrmann and Avidan, 2005;Duchaine and Nakayama, 2006b;Susilo and Duchaine, 2013). However, the nature and causes of the co-occurrence between ASD traits and DP are poorly characterized (Cygan et al, 2018). The goal of the present study was to examine whether DPs with higher levels of autism traits (i.e., broader autism phenotype, Wheelwright, Auyeung, Allison, and Baron-Cohen, 2010;Landry and Chouinard, 2016) differ from DPs with lower levels of autism traits across a broad battery of assessments, including face memory, face perception, holistic face processing, eye and mouth processing, emotion recognition, and in their fMRI selectivity and connectivity of face processing regions.…”
mentioning
confidence: 99%